Challenges of Conflicting School Reforms Effects of New American Schools in a High-Poverty District - Berends, Mark (RAND Corporation, 2002)
A decade ago, New American Schools (NAS) launched an ambitious effort forwhole-school reform to address the perceived lagging achievement of Americanstudents and the lackluster school reform attempts that have produced so fewmeaningful changes. As a private nonprofit organization, NAS set out tohelp schools and districts significantly raise the achievement of largenumbers of students by offering whole-school designs and design-basedassistance during the implementation process. NAS is currently in thescale-up phase of its effort, and its designs are being widely diffused toschools across the nation. During the 1997_1998 and 1998_1999 school years,RAND assessed the effects of NAS designs on classroom practice and studentachievement in a sample of schools in a high-poverty district. RAND foundthat high-poverty schools often have fragmented and conflicting environmentswith difficult and changing political currents and entrenched unions.Teachers in high-poverty schools tend to face new accountability systems andfluctuating reform agendas. These teachers generally lack sufficient timefor implementing reform efforts, often becoming demoralized and losing theirenthusiasm for the difficult task of improving student performance underdifficult conditions. RAND concluded that high-stakes tests may motivateschools to increase performance and to seek out new curricula andinstructional strategies associated with comprehensive school reforms.However, those same tests may provide disincentives to adopt richer, morein-depth curricula that can succeed in improving the learning opportunitiesof all students, particularly those in high-poverty settings.